Nilai Nilai Etika Filsafat Pendidikan Islam sebagai Solusi Krisis Identitas di Era Kontemporer - Asyifa Sanubari; Febrian Nasywa Anindya; Ismatul Khoeriah; Rodiyatul Qismah (Jurnal Budi Pekerti Agama Islam, 2026)
This article discusses ethical values in the philosophy of Islamic education as a response to contemporary challenges, such as moral crisis, declining character, and identity confusion. This study uses a literature review method with a philosophical and normative approach, based on Islamic teachings and the thoughts of educational figures. The results show that the philosophy of Islamic education contains important values such as monotheism, justice, responsibility, honesty, and good morals. These values are interconnected and play a significant role in shaping human personality. In addition to serving as a theoretical foundation, these values also function as guidelines in educational practice aimed at forming a complete human being (insan kamil). In the modern era, which is influenced by globalization and technological development, the application of Islamic ethical values is highly important to maintain a balance between intellectual intelligence and spiritual maturity. Therefore, the philosophy of Islamic education remains relevant as a solution for creating an education system that is not only intellectually advanced but also character-based and morally grounded. This study emphasizes that Islamic education needs to be directed toward the formation of moral awareness, the strengthening of spirituality, and the development of students’ social responsibility in daily life.